Pemanfaatan Mikroorganisme Antagonis untuk Mengendalikan Penyakit Hawar Bakteri (Xanthomonas campestris pv. malvacearum) pada Kapas - Titiek YULIANTI; Nurul HIDAYAH (Jurnal Pengendalian Hayati, 2008)
Bacterial blight of cotton caused by Xanthomonas campestris pv. malvacearum is oneof the important cotton diseases. The pathogen infects all of part of the plant from seedling to fullydevelop plant. In South Sulawesi, bacterial blight caused severe damage to the plant resulting yieldlost up to 50 %. Biological control is now a popular control method for plant diseases.This studyaimed to explore bacterial antagonists of bacterial blight. Exploration was conducted in Asembagus,Singosari and Karangploso. Bacteria were isolated from soil and cotton plant parts (root, sleaf, andstem). Six of 140 isolates were able to inhibit the growth of X. campestris pv. malvacearum in vitro.However, only 2 isolates (Asb-D-3 and Asb-D-5) have capability of reducing the disease severity on48,48% and 45,64% respectively.